Philippine folk literature : an anthology - Eugenio, Damiana L. (The U.P. Folklorists, Inc., Quezon City, 1982)
Students of Philippines culture have always lamented the scarcity of published collections of Philippine literature, especially of that fast vanishing species which we call oral, or folk, literature. This book aims to fill this need.
Introduction -- Folk Narrative: Myths -- Heroic Narratives (Folks Epics) -- Philippine Folk Literature : Legends -- Folktales :Animal Tales -- Fables -- Marchen (Tales of Magic) -- Philippine Folk Literature -- Folk Speech -- Folk Songs -- Non-Narrative Folk Songs -- Philippines Folk Literature.
Includes index.
Keywords: FOLK LITERATURE; FOLK LITERATURE -- PHILIPPINES